Proses Penciptaan Tari Cempaka (Bunga Ritual Sakral Masyarakat Bali) - Ni Wayan Suartini (Departement of Mathematics Education, 2023)
Cempaka Dance: The Sacred Ritual Flower of the Balinese Society, tells about human rites in dialogue with nature, spirits and gods. A performance art event that places and interprets the concept of space and time as an organic unity towards the movement of artistic awareness and the creation of events. Cempaka's choreography is a revitalization of Puri Anyar as a space that contains the concepts of Tri Hita Karana and Tri Mandala as spaces that open up creative ideas for choreographers in interacting with the Balinese cultural environment. This choreography is transformed into various forms of aesthetic elements; dance, song, music, decoration and symbolization of a traditional Balinese house in the form of a Puri (palace). The idea for the dance originates from the spatial function in Puri Anyar. Puri Anyar has historical value and beauty, is a traditional palace built based on the Tri Mandala and in accordance with Asta Kosala-Kosali or of adequate size and complete facilities for environmental choreography performances. Puri Anyar as a performance venue, the entire Puri area is used and responded to, there are no boundaries between the dancers and the audience, it is presented in the midst of the community, all the elements around the place become part of the structure of the performance. Through this Cempaka Dance, it is hoped that it can inform the development of Balinese culture, especially in the field of dance.